Toward a treatment for thyroid hormone transporter MCT8 deficiency – achievements and challenges - Boyka Markova; Steffen Mayerl; Heike Heuer (European Thyroid Journal)
Patients with an inactive thyroid hormone (TH) transporter MCT8 (Allan–Herndon–Dudley Syndrome, AHDS) display severe neurological impairments and motor disabilities, indicating an indispensable function of MCT8 in facilitating TH access to the human brain. Consequently, the CNS of AHDS patients appears to be in a TH deficient state, which greatly compromises proper neural development and function. Another hallmark of this disease is that patients exhibit elevated serum T3 levels, leading to a hyperthyroid situation in peripheral tissues. Several treatment strategies have been developed and evaluated in preclinical mouse models as well as in patients. Here, we discuss these different therapeutic approaches to overcome MCT8 deficiency and summarize the current achievements and challenges in improving brain maturation in the absence of MCT8.